Changing paradigms to address gender health inequities for all - Caroline Moreau; Kristin Mmari; Prerna Banati (Global Social Challenges Journal)
Gender health inequalities escalate during early adolescence, a critical period shaping lifelong health trajectories. Boys face heightened mortality, due to elevated rates of externalizing disorders such as conduct issues and substance use, while girls grapple with higher levels of internalizing disorders such as depression and sexual/reproductive health conditions, contributing to increased morbidity. Although global initiatives are bolstering gender equality to improve the well-being of women and girls and gender minorities, there remains little dedication to mitigating gender health disparities affecting boys and men. This lack of commitment is troubling, especially considering the increased evidence of harmful gendered exposures and behaviours that are affecting boys’ health and well-being, including disengagement in education, and increased mental health problems. In this commentary, we aim to examine recent evidence connecting gender norms to boys’ health throughout adolescence, encompassing both toxic and positive masculinity. We will assess the effectiveness and constraints of gender-transformative interventions in addressing boys’ health issues. Additionally, we will make the case for a paradigm shift in gender health research and adolescent programming, moving away from the gender binary while tailoring approaches to adolescents of all genders, expanding to their social environment.